The Influence of Value Innovation Strategy on the Financial Performance of Manufacturing Firms in Kenya - Maina, Kinyua; Mburugu, Kirema; Gachora, Susan (Academic Research Publishing Group, 2020)
Value innovation is the cornerstone of blue ocean strategy. Value innovation strategy aims at making competition irrelevant. The concept of value innovation strategy is founded on the belief that a business can make its competitors irrelevant in its decision making while at the same time emerging an industry leader. The purpose of this study is to establish the influence of Value Innovation Strategy on the financial performance of manufacturing firms in Kenya. The target population was 488 manufacturing firms drawn from the 12 categories of the sector in Kenya. Descriptive and inferential statistics were used in this study. The descriptive results indicate that the manufacturing firms in Kenya have implemented value innovation strategies which positively contribute to the financial performance of the firms. The inferential results also affirm that value innovation strategy significantly affect the performance of manufacturing firms in Kenya attributing up to 14.9% of its variation in performance. The study concludes that value innovation strategies boost financial performance of a firm. Managers of manufacturing firms should therefore implement value innovation strategies in order to improve financial performance
Keywords: Value innovation strategy; Manufacturing firms; Performance; Kenya